2021
DOI: 10.1111/jsr.13398
|View full text |Cite
|
Sign up to set email alerts
|

Altered brain activity related to inhibitory processing in youth with insomnia

Abstract: Insomnia, presented as problems with initiating or maintaining sleep, or early morning awakening, affects about 33.7% to up to 69% of the youth population, depending on the defining criteria and age of the study samples (Blank et al., 2015;Chung, Kan, & Yeung, 2014;Sing & Wong, 2011). Insomnia in youth entails an increased risk of developing a wide range of negative outcomes, including interpersonal problems, poor perceived physical health, somatic health problems, as well as depressive and anxiety symptoms (B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…It was possible that mild sleep variability might not be sufficient to induce changes in cognitive abilities at a behavioural level. In this regard, a recent study showed that youth with insomnia had a comparable performance on the cued go/no-go task as compared with healthy sleepers, but showed altered brain activities as measured by event-related potential, suggesting impaired inhibitory control (Ling et al, 2021). Future studies with neuroimaging techniques are needed to further examine possible underlying changes in brain activity in response to sleep variability.…”
Section: Effects Of Irregular Sleep Schedule On Daytime Functioningmentioning
confidence: 99%
“…It was possible that mild sleep variability might not be sufficient to induce changes in cognitive abilities at a behavioural level. In this regard, a recent study showed that youth with insomnia had a comparable performance on the cued go/no-go task as compared with healthy sleepers, but showed altered brain activities as measured by event-related potential, suggesting impaired inhibitory control (Ling et al, 2021). Future studies with neuroimaging techniques are needed to further examine possible underlying changes in brain activity in response to sleep variability.…”
Section: Effects Of Irregular Sleep Schedule On Daytime Functioningmentioning
confidence: 99%
“…N2 is localized in the frontal, central, and temporal regions [ 9 ], and the amplitude of N2 represents the degree of emotional sharing of empathy for others’ pain [ 20 ]. Additionally, Ling et al [ 21 ] discovered reduced N2 amplitudes in insomniacs during the Go/No-go task, suggesting potential deficits in attentional and inhibitory control. LPC, localized in the posterior parietal lobe, represents a stage of cognitive processing and evaluation of others’ pain like that of P3 [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…These suggest the impairment of motor inhibition among individuals with insomnia. A recent study (14) combined a go/no-go task and EEG to measure adolescents with insomnia. The results showed that adolescents with insomnia showed altered brain activity during inhibitory control.…”
Section: Introductionmentioning
confidence: 99%